Cognitive reflections in children with ADHD and proposals to promote logical thinking - Salvatierra Melgar, Ángel (2021)
The present study shows the need to reflect on the sequences of cognitive processes of logical thinking in children with ADHD, andit also provides strategies to promote them. The research was carried out on a sample of 11 children with ADHD within the ages of 5 and 6, identified by the checklist of the DSM_IV in addition to the interview sessions with their teachers and classmates. Due to the characteristics described, the study is based on the qualitative approach of ethnographic design and documentary review. It was concluded that these children often make frequent errors in the resolution of logical operations due to lack of attention and concentration during the algorithmization of arithmetic operations. They cannot combine the implicit data of situations in problems with literal statements, and they also show a high level of dyscalculia. On the other hand, the learning of these children is manifested with the manipulation of concrete materials, documents with clear and colorful texts, activities with serial games, which allow activating their attention by means of graphics, silhouettes, guides and sequences with defined procedures for the achievement in following instructions. © 2021 Turkish Physiotherapy Association. All rights reserved.